Experimental investigation of two-phase separation in a horizontal T-junction with vertical branch arm - Z. Q. Memon; W. Pao; F. Hashim; S. Ahmed (Journal of Mechanical Engineering and Sciences, 2019)
T-junctions are commonly used in offshore platforms and process industry. When two-phase flow passes through T-junction, separation of two-phases takes place. This separation of two-phase flow through T-junction produces high liquid carry-over in the branch arm, causing breakdown of downstream equipment. In this experimental study, phase separation data have been obtained for air-water mixture flow through dividing T-junction with a pipe diameter of 74 mm and the branch arm is positioned vertically upward. T-junctions with diameter ratios of 1, 0.67, 0.5, and 0.27 were tested in the slug flow regime. The superficial velocities of air (JG1) were varied 0.20 - 1.16 m/s and inlet water superficial velocities (JL1) were varied 0.40-0.53 m/s. The extraction ratio between branch arm and main arm (W3/W1) was varied between 0 to 1. It was observed that the phase separation efficiency of T-junction depends upon the diameter ratio, upstream superficial velocities of both phases - air and water. Finally, the experimental data have been compared against the predicted results obtained from the numerical correlations.